Importance of Exercise in Mitigating Age-Related Cardiac Apoptosis: English - Mustika Anggiane Putri; Patwa Amani; Donna Adriani; Rita Khairani (Sriwijaya Journal of Medicine, 2023)
Aging causes a progressive decline in heart function. Loss of cardiomyocytes through programmed cell death or apoptosis is a critical factor contributing to this age-related damage. As we age, the heart undergoes structural changes, such as loss of cardiomyocytes, cardiomyocyte hypertrophy, and increased connective tissue with changes in heart geometry. It is widely known that mitochondria are vital sites of apoptosis. Mitochondrial-mediated apoptotic pathways are important regulators of apoptosis with aging. Mitochondrial dysfunction and oxidative stress also contribute to the cardiac remodeling and apoptosis associated with the aging process. On the other hand, exercise can improve heart function and reduce the risk of heart disease. Recent studies suggest that aging increases apoptotic signaling in the left ventricle. However, chronic exercise reduces this mitochondrial-mediated apoptotic signaling pathway in the aging heart. This review will describe the impacts of aging and exercise on cardiac apoptosis, highlighting the importance of exercise in reducing age-related cardiac apoptosis.